IoT based Vehicle Management System using ESP32 - Aman,; Rahul,; Pankaj Sharma,; Anil Jindal, (International Journal of Engineering and Management Research, 2023)
This project aims to develop an Internet of Things (IoT) based vehicle management system using ESP32 microcontroller to track the location, speed, and direction of a vehicle in real-time. The system utilizes GPS module, Reed switch, Gyroscope and accelerometer to capture the location, number of gear, direction of vehicle and speed data respectively, while the Wi-Fi module is used to transmit the data to a cloud server for storage and analysis. The system is designed to be scalable and cost-effective, making it suitable for a wide range of vehicle tracking applications. The results of the project show that the system can accurately track the location and speed of the vehicle and provide real-time information to the user, making it an efficient and reliable solution for vehicle management.